STUDIES ON THE PRECIPITIN REACTION : PRECIPITATING HAPTENS; SPECIES DIFFERENCES IN ANTIBODIES - Heidelberger, Michael (The Rockefeller University Press, 1933)
1. Partial hydrolysis products of the specific polysaccharide of Type III pneumococcus ranging from 550 to 1,800 in formula weight can be quantitatively freed from unhydrolyzed polysaccharide. 2. The fractions yield specific precipitates with Type III antipneumococcus horse serum but fail to precipitate homologous rabbit antisera, giving rise only to specific inhibition. The aldobionic acid, the structural unit of S III, does not precipitate antisera. 3. A possible explanation and a possible application of the findings are pointed out.